Effect of growing conditions, time of pollination and fruit retention in hybrid seed production of summer squash (Cucurbita pepo) - KUNJ BIHARI AHEER; BALRAJ SINGH; B.S. TOMAR; MUKUL KUMAR (Seed Research, 2026)
An investigation was carried out under insect proof net house (IPN) and open field at Centre for Protected Cultivation Technology (CPCT), IARI, New Delhi in hybrid seed production of summer squash (Cucurbita pepo L.) cv. Pusa Alankar showed that number of leaves, leaf area and female flower were more in insect proof net house. Significantly higher number of fruits set and matured fruits/plant was registered in insect proof net house. Among the fruit development and seed yield characters viz. fruit weight (1179.90 g), fruit length (34.19 cm), number of seeds/fruit (343.70), number of filled seeds/fruit (333.60), seed yield/fruit (38.47 g), seed yield/plant (73.09 g) and seed yield/ha (1096.42 kg) were significantly higher under insect proof net house. Among the physical parameters of seed viz. seed width, seed coat weight showed significant differences. The seed quality attributes were also significantly superior under insect proof net house except germination%. Pollination at 6 am established better fruit development, seed quality and seed yield under insect proof house. Retention of two fruits/plant gave higher seed yield/plant (60.51 g) and seed yield/hectare (908.55 kg) than those of one fruit/plant (40.21 g & 603.15 kg, respectively). Seed quality attributes were higher, if one fruit/plant was retained. The incidence of virus was zero under IPN, whereas 60% plants were affected with virus at maturity under open field conditions.